PROMISING DIRECTIONS IN SELECTION OF MARROW - A. M. Shantasov; S. D. Sokolov; A. N. Bocharnikov; A. S. Sokolov; N. G. Izmukhambetova; Zh. R. Nugmanova (Овощи России, 2018)
In recent years the interest of the Russian citizens in “healthy diet” has been growing. An important role in this matter can play a low-calorie marrow squash considered as a dietary product, but rich with a lot of useful vitamins and saline minerals. In the selective seed-production enterprise “Master Semya” it is placed a high emphasis on the creation of varieties and F1 hybrids not only productive, but also attractive and eyecatching, with a high level of biochemical features. Within the research it was selected three maternal lines of a marrow and carried out the estimation of their overall combinational ability for yielding capacity and biochemical parameters. There were given recommendations on their use in the selection of F1 hybrids. The high values of overall combinational ability for the characteristics of “content of solid matter” and “sugar amount” were distinguished on the maternal line GRS ms. While assessing the economic utility of F1 hybrids of this maternal line, the attention should be paid to the manifestation of a specific combinational ability for productivity. On the characteristics of “yielding capacity of fruits” and “ascorbic acid content” it was noted a hybrid progeny of the maternal line GRA ms. Selections for specific combinational ability have to be made for a characteristic of high content of solid matter. The maternal line GRL ms has an average data on overall combinational ability for all the studied characteristics. Selections should be conducted according to certain distinguished combinations. The hybrid combinations were evaluated for the main agronomic features and pointed out the promising ones for industrial processing. For the sale in a fresh form and home cooking it is recommended marrow variety “Astor” as productive, with high biochemical characteristics, keeping the marketable qualities for a long time.